Establishing and prioritizing research questions for the treatment of alopecia areata: the Alopecia Areata Priority Setting Partnership. (16th April 2017) - Macbeth, A.E.; Tomlinson, J.; Messenger, A.G.; Moore‐Millar, K.; Michaelides, C.; Shipman, A.R.; Kassim, J.M.; Brockley, J.R.; Szczecinska, W.; Farrant, P.; Robinson, R.; Rodgers, J.; et al.
Abstract : What's already known about this topic? Many uncertainties exist around the management and treatment of alopecia areata (AA). What does this study add? We present the top 10 uncertainties in AA management and treatment that are important to service users (people with hair loss, their carers and relatives) and healthcare professionals. These prioritized research uncertainties can be used to guide researchers and funding bodies when deciding to invest in AA research studies. Respond to this article Linked Comment:Apfelbacher. Br J Dermatol 2017; 176:1128–1129 Plain language summary available online Summary: Background: Alopecia areata (AA) is a common hair loss disorder that results in patchy to complete hair loss. Many uncertainties exist around the most effective treatments for this condition. Objectives: To identify uncertainties in AA management and treatment that are important to both service users (people with hair loss, carers and relatives) and healthcare professionals. Methods: An AA priority setting partnership was established between patients, their carers and relatives, and healthcare professionals to identify the most important uncertainties in AA. The methodology of the James Lind Alliance was followed to ensure a balanced, inclusive and transparent process. Results: In total, 2747 treatment uncertainties were submitted by 912 participants, of which 1012 uncertainties relating to AA (and variants) were analysed. Questions were combined into 'indicative uncertainties' following a structured format. A series of ranking exercises further reduced this list to a top 25 that were taken to a final prioritization workshop where the top 10 priorities were agreed. Conclusions: We present the top 10 research priorities for AA to guide researchers and funding bodies to support studies important to both patients and clinicians.